1999
DOI: 10.1902/jop.1999.70.7.772
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD14‐Dependent Intercellular Adhesion Molecule‐1 Induction by Porphyromonas gingivalis Lipopolysaccharide in Human Gingival Fibroblasts

Abstract: These results indicate that P. gingivalis LPS induces ICAM-1 expression in HGF in an sCD14-dependent manner. The overexpression of ICAM-1 on fibroblasts in gingiva induced by P. gingivalis LPS seems to be involved in the retention of inflammatory cells in periodontitis lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The anti‐CD14 antibody experiments suggest that the CD14 pathway may play a crucial role in the mechanism of P. gingivalis ‐mediated chemokine induction. Previous studies have also demonstrated that human gingival fibroblasts were activated by P. gingivalis through a CD14‐dependent mechanism [14, 42]. In our study, membrane CD14 expressed on endothelial cells [43] and/or soluble CD14 in culture medium were considered to be involved in the stimulatory effect of P. gingivalis .…”
Section: Discussionsupporting
confidence: 53%
“…The anti‐CD14 antibody experiments suggest that the CD14 pathway may play a crucial role in the mechanism of P. gingivalis ‐mediated chemokine induction. Previous studies have also demonstrated that human gingival fibroblasts were activated by P. gingivalis through a CD14‐dependent mechanism [14, 42]. In our study, membrane CD14 expressed on endothelial cells [43] and/or soluble CD14 in culture medium were considered to be involved in the stimulatory effect of P. gingivalis .…”
Section: Discussionsupporting
confidence: 53%
“…LPS from periodontopathic bacteria induced secretion of inflammatory cytokines by human polymorphonuclear leukocytes [Yoshimura et al, 1997]. P. gingivalis LPS induces intercellular adhesion molecule‐1 (ICAM‐1) expression in human gingival fibroblasts in a soluble CD14 dependent manner [Masaka et al, 1999]. These findings suggest that LPS is one of the crucial factors in periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The soluble form of CD14 has also been investigated as a potential effector molecule in the interaction of the host and periodontopathogens. It has been reported that P. gingivalis LPS induces adhesion molecule expression in human gingival fibroblasts in a sCD14‐dependent manner (Masaka et al 1999). Soluble CD14 seems to mediate the response to LPS in cells lacking mCD14.…”
Section: Discussionmentioning
confidence: 99%